Rekontekstualisasi Madilog Tan Malaka dalam Ruang Publik Virtual: Studi Kasus Konten Youtube MALAKA : Recontextualization of Tan Malaka's Madilog in Virtual Public Space: A Case Study of MALAKA's YouTube Content - Muklis Siregar; Amroeni Drajat; Hasnah Nasution; Agung Prayogo (Undiksha, 2026)
This article examines the recontextualization of Tan Malaka's Madilog in fostering rational-scientific reasoning within the contemporary digital society. The YouTube channel